Anaphothrips cocos sp.n. (Thysanoptera, Thripinae) from coconuts in Timor Leste - Mound, Laurence A. (Zootaxa, 2021)
The Anaphothrips genus-group is a complex of 40 genera of Thripinae that share the condition of “no long pronotal setae”. In traditional Thysanoptera classifications this absence of long pronotal setae was interpreted as a plesiomorphy by comparison to the condition in Aeolothripidae. Thus Jacot-Guillarmod (1974) catalogued all Thripinae genera with species showing this condition in a sub-tribe Aptinothripina Karny, a long-established arrangement that had been adopted by many authors. However, a study by Buckman et al. (2013) confirmed that taxa in the families Merothripidae and Melanthripidae share an important number of structural plesiomorphies, and these taxa all have long pronotal setae. From this it is concluded that absence of long pronotal setae is a derived condition, and moreover this loss apomorphy has arisen independently within several unrelated genera, such as Dichromothrips, Trichromothrips and Thrips (Mound & Palmer 1981; Mound & Masumoto 2004, 2005). As a result, it is possible that the Anaphothrips genus-group does not represent a single lineage, and that not all of the included genera are closely related.